2018 International Consensus Meeting on Musculoskeletal Infection: Research Priorities from the General Assembly Questions. Issue 5 (25th April 2019) - Schwarz, Edward M.; Parvizi, Javad; Gehrke, Thorsten; Aiyer, Amiethab; Battenberg, Andrew; Brown, Scot A.; Callaghan, John J.; Citak, Mustafa; Egol, Kenneth; Garrigues, Grant E.; Ghert, Michelle; Goswami, Karan; et al.
ABSTRACT: Musculoskeletal infections (MSKI) remain the bane of orthopedic surgery, and result in grievous illness and inordinate costs that threaten healthcare systems. As prevention, diagnosis, and treatment has remained largely unchanged over the last 50 years, a 2nd International Consensus Meeting on Musculoskeletal Infection (ICM 2018, https://icmphilly.com ) was completed. Questions pertaining to all areas of MSKI were extensively researched to prepare recommendations, which were discussed and voted on by the delegates using the Delphi methodology. The questions, including the General Assembly (GA) results, have been published (GA questions ). However, as critical outcomes include: (i) incidence and cost data that substantiate the problems, and (ii) establishment of research priorities; an ICM 2018 research workgroup (RW) was assembled to accomplish these tasks. Here, we present the result of the RW consensus on the current and projected incidence of infection, and the costs per patient, for all orthopedic subspecialties, which range from 0.1% to 30%, and $17, 000 to $150, 000. The RW also identified the most important research questions. The Delphi methodology was utilized to initially derive four objective criteria to define a subset of the 164 GA questions that are high priority for future research. Thirty‐eight questions (23% of all GA questions) achieved the requisite > 70% agreement vote, and are highlighted in this Consensus article within six thematic categories: acute versus chronic infection, host immunity, antibiotics, diagnosis, research caveats, and modifiable factors. Finally, the RW emphasizes that without appropriate funding to address these high priority research questions, a 3rd ICM on MSKI to address similar issues at greater cost is inevitable.